2018
DOI: 10.1136/bcr-2017-221550
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral tension pneumothorax after acupuncture

Abstract: Acupuncture is an ancient complementary medicine which is currently used worldwide. Many serious adverse events have been reported which include a spectrum of mild-to-fatal complications. However, the level of awareness with regard to complications is still low both to physicians and patients. We report a 63-year-old who presented with acute shortness of breath 2 hours after having had acupuncture. On examination, there was absent breath sound heard on the left lung and slightly reduced breath sound on the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Healthcare professionals should maintain a high level of suspicion of hemothorax, pneumothorax, or both when a patient reports dyspnea, chest pain, or interscapular pain following acupuncture in the thoracic area [ 18 ]. Pneumothorax may require invasive intervention and ongoing monitoring because it has the potential to develop into a critical condition that may compromise cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals should maintain a high level of suspicion of hemothorax, pneumothorax, or both when a patient reports dyspnea, chest pain, or interscapular pain following acupuncture in the thoracic area [ 18 ]. Pneumothorax may require invasive intervention and ongoing monitoring because it has the potential to develop into a critical condition that may compromise cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Severe complications from needling techniques are rare but potentially life-threatening 14 17–20. In 2020, Boyce et al 8 looked at 20 464 dry needling treatments and found 7531 (36.7%) minor adverse events and 20 (<0.1%) major adverse events, including six cases of prolonged symptom aggravation, four cases of fainting, three cases of forgotten needles, two cases of influenza like symptoms, two cases of infection, one case of excessive bleeding, one case of lower limb weakness and one case of numbness.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax is the most common of the serious adverse events and is likely to go unreported7 although some can be as critical as bilateral pneumothorax 13–15…”
Section: Discussionmentioning
confidence: 99%